The Value Of Character education in the Novel Of The Dreamer by Andrea Hirata and Its Relevance to the Education Process in Elementary Schools - Fransiska Jaiman Madu (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Purwokerto, 2020)
The background of this research is the importance of character education in human life being able to shape one's personality, identity and character so as to have a balanced ability between thoughts and feelings, emotionality and intellect. realize the application of character education there are many ways that are done through education, literary works, etc. but in this case, the researcher was inspired to analyze the values of karaker education contained in a literary work in the form of a novel that is the Dreamer novel by Andrea Hirata and found the relevance of the character education values contained in the Dreamer novel withthe values of character education for the educational process in Cluster 4 Langke Rembong DistrictThis study aims to analyze the values of character education contained in the novel Sang Pemimpi and find the relevance of the values of character education contained in the novel Sang Pemimpi with the values of character education for the educational process in Cluster 4 DistrictLangke Rembong.This research is a descriptive study with a qualitative approach and content analysis methods through data collection techniques in the form of text analysis, document studies and interviews.The results of the study found twelve character education values contained in the novel The Dreamer of eighteen character education while six other character values were not found by the writer in the novel Dreamer. the twelve values of character education contained in the novel The Dreamer that is in relation to God, including religious values, in relation to oneself including the values of discipline, the value of hard work, creative values, independent values, the value of curiosity, the value of responsibilityanswer, the value of respecting achievement and in relation to others includes the value of tolerance, the value of friendship / communicative, and the value of social care. in addition to analyzing the values contained in the novel The Dreamer the researcher also conducted research in the form of interviews in Cluster 4 Langke Rembong District. The sources of interview data are the principal, grade 5 teachers and grade V. studentsbased on the analysis of the values of character education contained in the novel Sang Pemimpi, with the values of character education applied in Cluster 4, Langke Rembong District. shows relevance.